Study of Biodiversity of the Arak University Watershed - Amir Ansari (Journal of Sustainability Perspectives, 2021)
Biodiversity has declined in many areas because of human activities and loss of habitats. The Watershed of Arak University with a total area of 625.65 hectares is located on the southwestern slope of Mount Mudar, northwest, adjacent of Arak city and north of Karahrod. Biodiversity information of the area was collected with using linear transect and dotted transect methods by installing camera trap, camera and GPS. The results indicate that biodiversity history dates back more than 65 million years. Currently, lives 55 species of dominant rangeland species and 50 species of animal include: 34 species of birds, 10 species of mammals and 6 species of reptiles and amphibians in the area. Falcon and Fritillaria are the Endangered (EN) and Greek tortoise and persian toad agama are the Vulnerability (VU). The most important threats to biodiversity include are development of the city of Arak in the region, habitat destruction, uncontrolled hunting, livestock and dogs, road construction and the abandonment of habitats with surrounding habitats, feeding wildlife from urban waste, nature tourism and informal climbing.